Afamelanotide in protoporphyria and other skin diseases: a review - Polańska, Adriana; Wegner, Joanna; Nutbohm, Paula; Staubach, Petra; Żaba, Ryszard; Dańczak-Pazdrowska, Aleksandra; Jenerowicz, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2024)
Afamelanotide is a synthetic alpha melanocyte stimulating hormone presenting a higher activity than natural hormones. Its main properties are related to the enhanced production of eumelanin by agonistically binding to the melanocortin-1 receptor. Since 2016 afamelanotide has been especially applied to treat cases of erythropoietic porphyria (EPP), where painful photosensitivity has been observed since early childhood. The positive effect of afamelanotide in EPP administered subcutaneously improved tolerance to artificial white light and increased pain-free time spent in direct sunlight. In this review we summarize the possible use of afamelanotide in dermatology, with special emphasis on EPP and encourage including afamelanotide as a treatment option in patient care.